Factors affecting the adoption of shared mobility systems: Evidence from Australia. (December 2021) - Jie, Ferry; Standing, Craig; Biermann, Sharon; Standing, Susan; Le, Thi
Abstract: The purpose of this paper is to examine the current impact and potential of the various forms of shared mobility, with a focus the shire of Wanneroo in Western Australia. Shared mobility options included in the study are car-pooling, ride-sourcing, car-sharing and bike-sharing. Residents of Wanneroo were asked about their use of shared mobility, their intended behaviour in the future, their views on the benefits, barriers to adoption, and their shared mobility use in travel to/from rail stations. Results show that a significant percentage of respondents had used shared mobility options, and the primary use of shared mobility was for social activities and secondly, work-related activities; a higher percentage of respondents said they were positive about shared mobility and would use it in the future. The findings indicate that gender is the most important driver to predict whether an individual will or will not use shared mobility. Employment status, annual income, attitude towards benefits of shared mobility, the capability to access shared mobility, and reasons for shared mobility have a positive correlation to the possibility of shared mobility use. Finally, the study reports that respondents are positive about the use of shared mobility options for travelling to and from the rail station. Highlights: A survey of residents in the shire of Wanneroo revealed that overall people were positive about using shared mobility. Women are greater users of shared mobility except for bike sharing. Higher income groups were more likely to use shared mobility options. Those physically able to use and confident in arranging shared mobility use were more positive about using shared mobility. Respondents were positive about the use of shared mobility options for travel to and from the railway station.